Sustainable ecotourism development strategy for the municipality of Sutatausa, Cundinamarca - Colombia by 2034 - Santa Rodriguez, Hugo Orlando; Sapuyes Chávez, Tania Alejandra (Universidad Francisco de Paula Santander, 2024)
This article aimed to propose a strategy for sustainable ecotourism development in the municipality of Sutatausa, Cundinamarca, Colombia. The methodological design followed a mixed approach, where the quantitative scope was exploratory, and the qualitative approach involved participatory action research through the community strategic prospective methodology. Workshops were conducted to gather information, employing brainstorming techniques and SWOT analysis for diagnosis. Subsequently, structural analysis of strategic trends in ecotourism was performed using Scopus closed databases, and a 5W2H action plan was devised. Micmac was used for systematization. As a result, the proposed strategy involves formulating a public tourism policy based on sustainable ecotourism of goods, tourist attractions, and cultural heritage in the municipality of Sutatausa. In conclusion, the proposal reflects a visionary and responsible approach to tourism development. The implementation of sustainable tourism practices aims to boost the local economy. Furthermore, this initiative provides an opportunity to balance economic growth with environmental conservation, promoting tourist experiences that respect and value the rich biodiversity and cultural heritage of Sutatausa. By integrating sustainability principles into tourism organization and management, the goal is to minimize adverse consequences for the environment.